Analisis Hubungan Tenaga Kerja dan Pendapatan terhadap Perkembangan Industri Wisata di Desa Gosari Gresik - Fardana, Andrew Ari; Sitohang, Arga Christian (Nirta Learning Centre, 2024)
The tourism industry in Indonesia is an important economic sector that makes a significant contribution to national income and creates job opportunities. For example, Gosari Village, which is located in Gresik Regency, East Java, is one of the village tourist destinations that is increasingly developing and receiving attention. Village tourism in Gosari combines the rich culture, history and natural beauty typical of the Gresik region. One of the main attractions of Gosari Village is the presence of historical sites such as the Petilasan Sunan Kalijaga and the Giri Kedaton Site, which have high historical value related to the spread of Islam in Java. This type of research uses quantitative with a descriptive approach. Using multiple linear regression models using primary data. The aim of this research is to analyze the influence of labor and income on the tourism industry in Gosari Gresik village. The results of this research show that labor and income have a significant influence on the development of the Gosari Gresik village tourism industry.